Farmer Field Day in Kathonzweni, Makueni - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
On 16th July 2014 farmers from Makueni and Kitui Counties, visited different trial sites during a farmer field day event, to select the best sorghum varieties, this was after a research Project testing climate change resilience of sorghum varieties from National gene banks of Kenya and Tanzania. The project was supported by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and was conducted by the African (ABCIC) and Bioversity international. Photos: S.Kilungu (CCAFS)